2009
DOI: 10.1001/archgenpsychiatry.2009.55
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Family History on Severity of Illness

Abstract: Context If family history is associated with clinical features that are thought to index seriousness of disorder, this could inform clinicians predicting patients’ prognosis and researchers selecting cases for genetic studies. Although tests of associations between family history and clinical features are numerous for depression, such tests are relatively lacking for other disorders. Objective To test the hypothesis that family history is associated with 4 clinical indexes of disorder (recurrence, impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 104 publications
8
73
2
1
Order By: Relevance
“…The latter is of particular importance given that relapse continues to be a significant challenge to clinicians (Keller et al, 1982; Dobson and Ottenbreit, 2004). A number of biopsychosocial factors have been implicated in increasing relapse risk including genetic loading with mood disorders, co-morbid medical and psychiatric conditions and substance use, psychosocial stressors, and personality coping styles (Klein et al, 2004; Milne et al, 2009; Zisook et al, 2004; Riise and Lund, 2001; Kivelä et al, 2000). Furthermore, baseline symptom severity, duration of illness, number of depressive episodes, duration of depressive episode, and number of medication trials until remission play an important role as well (Pintor et al, 2004; Mulder et al, 2006; Holma et al, 2008; Greer et al, 2010; Rush et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is of particular importance given that relapse continues to be a significant challenge to clinicians (Keller et al, 1982; Dobson and Ottenbreit, 2004). A number of biopsychosocial factors have been implicated in increasing relapse risk including genetic loading with mood disorders, co-morbid medical and psychiatric conditions and substance use, psychosocial stressors, and personality coping styles (Klein et al, 2004; Milne et al, 2009; Zisook et al, 2004; Riise and Lund, 2001; Kivelä et al, 2000). Furthermore, baseline symptom severity, duration of illness, number of depressive episodes, duration of depressive episode, and number of medication trials until remission play an important role as well (Pintor et al, 2004; Mulder et al, 2006; Holma et al, 2008; Greer et al, 2010; Rush et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A substance use disorder was defined as current or lifetime drug and/or alcohol abuse and/or dependence. At the final block, we entered the risk variables, which included family history of an anxiety disorder in a first-, second- or third-degree relative (dichotomous) [29,30,31] and current treatment with clozapine (dichotomous). Clozapine was entered as a risk variable due to its association with the development of anxiety disorders [32,33,34].…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of data from a prospective New Zealand birth cohort of nearly 1000 individuals has shown that family history is a strong predictor of AUD and is associated with a more recurrent course and worse impairment [15]. It is well known that an important risk factor is having an alcoholic parent.…”
Section: Heritabilitymentioning
confidence: 99%